A detailed kinetic and mechanistic investigation of the multi-step oxidation of [PtIICl4]2- by [IrIVCl6]2- in acidic medium - Van Dyk, Jacobus Barend (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.